(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: The diagnosis of mechanical intestinal obstruction is sometimes very challenging especially in the absence of previous abdominal surgery or obstructed hernia and there are limited studies comparing or evaluating the usefulness of plain abdominal x-ray, ultrasonography, and computerized tomography (CT) in intestinal obstruction. Objective: To compare the efficacy of plain abdominal x-ray, ultrasound and CT in the diagnosis of intestinal obstruction. Also, to assess ultrasound value and usefulness in pregnant women and critically bed ridden patients with intestinal obstruction. Methods: In this prospective study with signs and symptoms of mechanical intestinal obstruction, a total of sixty two patients were investigated by plain x-ray, ultrasound, CT scan and the findings were compared with reference to the presence or absence of obstruction, the level, site, cause and strangulation of bowel for a period of eight years (2009-2016). The final diagnosis was obtained by surgery and only those with proved intestinal obstruction per-operative were included in the study. Results: Out of the sixty two patients (41 males and 21 females) included with an age incidence (22-65 yr), 58 had mechanical intestinal obstruction (50 had small bowel obstruction and 8 had large bowel obstruction), of the remaining 4 patients; 2 had mesenteric vascular occlusion and 2 had pseudo-obstruction. The level and site of obstruction was correctly predicted in 91.9% on CT, in 82% on ultrasound and 90.3% on plain film. CT was the best 85.4% to both, ultrasound 24% and plain film 8% in determining the cause of obstruction. Regarding strangulation of bowel, CT was superior while plain film was the least informative with the ultrasound in between. Conclusion: CT is the best tool for the diagnosis, strangulation of the bowel and detecting cause of intestinal obstruction and recommended to be the investigation of choice in equivocal cases. Ultrasound is the best and sole investigation in pregnant women and critically bed ridden patients especially in early cases. Keywords: Intestinal obstruction, plain abdominal x-ray, ultrasound, CT scan. Citation: Salih NK. Value of plain abdominal radiograph, ultrasound and computerized tomography in the diagnosis of intestinal obstruction. Iraqi JMS. 2017; Vol. 15(3): 227-233. doi: 10.22578/IJMS.15.3.3